The Impact of Expert Systems on Reducing Electronic Fraud: A Field Study at Al-Jumhouria Bank – Tripoli (Comprehensive Journal of Science, 2026)
The study aimed to analyze the impact of expert systems in reducing electronic fraud in commercial banks in the city of Tripoli. The study relied on expert systems as the independent variable, and electronic fraud as the dependent variable. A simple random sample of 125 individuals was selected, with 120 questionnaires analyzed using SPSS software after excluding 5 for incompleteness. It followed the descriptive analytical approach to interpret the relationship between the variables. The study concluded that the knowledge base in expert systems comprehensively covers banking procedures related to credit evaluation, risk management, and fraud detection, with high accuracy and reliability. It recommended enhancing the knowledge base by periodically updating it with data from reliable sources to keep pace with developments in banking procedures
Keywords: Expert systems – Electronic fraud.